Pre-treatment Strategies for Value Addition in Poultry Litter - Gaspareto, Taís Carla; Scapini, Thamarys; Venturin, Bruno; Tápparo, Deisi Cristina; Camargo, Aline Frumi; Luccio, Marco Di; Valerio, Alexsandra; Favretto, Rafael; Antes, Fabiane Goldschmidt; Steinmetz, Ricardo Luís Radis; Treichel, Helen; Kunz, Airton (Frontiers in Bioengineering and Biotechnology, 2020)
We studied different pre-treatments of poultry litter aiming to add economic value to this residue. Strategies were applied to extract ammonium nitrogen with the aim of allowing its further use as fertilizer, and to promote the hydrolysis and solubilization of lignocellulosic components with the aim of facilitating its subsequent conversion to biogas. Ammonia extraction was performed by solubilization in water in a one-step process and by successive extraction steps (3 times 60 min). Successive extractions presented greater removal of total ammonia nitrogen than did one-step extraction, solubilizing about 36% of the ammonia in water. In parallel pre-treatment using ultrasound was performed to increase carbon bioavailability for anaerobic digestion. Using this tool, 24.7 g kg-1 of total organic carbon and 13.0 g kg-1 of total reducing sugars were solubilized, employing 10% dry mass sample amount, 100% ultrasound at frequency of 20 kHz amplitude and 2.5 minutes of treatment (energy input of 299 ± 7 kJ L-1; 3822 ± 95 kJ kg-1). Anaerobic digestion of ultrassound pre-treated biomass was evaluated using a biological biogas production assay, and an increase of 10% of biogas production was obtained compared to untreated samples (147.9 and 163.0 mL g-1 for crude and pre-treated PL, respectively). The findings suggest that these are environmentally friendly and sustainable strategies to add economic value to poultry litter, reducing the environmental impacts of improper disposal.